Genome‐wide identification of WOX family members in rose and functional analysis of RcWUS1 in embryogenic transformation - Xue Bai; Qi Fu; Weikun Jing; Hao Zhang; Hongying Jian; Xianqin Qiu; Hongjie Li; Qigang Wang; Shunting Yang; Yiping Zhang; Huichun Wang; Lihua Wang; et al. (The Plant Genome)
Abstract WUSCHEL‐related homeobox (WOX) is a class of plant‐specific transcription factors and plays vital roles in plant development and evolution. Here, we analyzed WOX family genes of three Rosa species and explored their potential functions in Rosa. A total of 351 WOX genes were identified from Rosa chinensis ‘Old Blush’ (208), Rosa wichuraiana ‘Basye's Thornless’ (21) and Rosa rugosa (122). The WOX genes were found to significantly expand in Rosa compared to Arabidopsis. Phylogenetic analysis showed that Rosa WOXs genes were classified into an ancient clade, an intermediate clade, and a WUS clade. Collinearity analysis suggested that gene duplication and purifying selection might be important driving forces in the evolution of WOXs. Expression patterns of WOXs found that higher levels of RcWUS1 expression were detected at the shoot apex somatic embryos. Furthermore, we found that RcWUS1 was a transcriptional repressor located in the nucleus. Overexpression of RcWUS1 enhanced the regeneration efficiency of somatic embryos. In summary, our results indicated the functional potential of RcWUS1 in embryogenic transformation, which can be further utilized to improve the genetic transformation efficiency in rose.